Recurrent and de novo glomerulonephritis following renal transplantation: higher rates of rejection and lower graft survival - MİRİOĞLU, ŞAFAK; Mirioglu, ŞAFAK; Caliskan, Yasar; Goksoy, Yagmur; Gulcicek, Sibel; Ozluk, Yasemin; Sarihan, Irem; Seyahi, Nurhan; KILIÇASLAN, Işın; TÜRKMEN, Aydın; SEVER, Mehmet Şükrü (My University, 2017)
In this retrospective study with case-control design, we aimed to determine the clinical and pathological characteristics of post-transplant glomerulonephritis (GN), and their effects on transplant recipients.